Comparisons of physical characteristics and performances among female collegiate rowers - Battista, R. A.; Pivarnik, J. M.; Dummer, G. M.; Sauer, N.; Malina, R. M. (Journal of Sports Sciences, 2007)
The physical characteristics and performances of female collegiate rowers were examined from two perspectives: level (novice, varsity) and years of participation (0, 1, 2, 3) in collegiate rowing. The participants were 90 female collegiate rowers from three US Division I university teams, of the National Collegiate Athletic Association (NCAA). Height, body mass, sitting height, arm span, skinfolds, limb circumferences, and skeletal breadths were measured. Leg length was estimated and Heath-Carter anthropometric somatotypes were calculated. Performance measures included lower-back flexibility, vertical jump, and 2-km time on a rowing ergometer. Descriptive statistics were calculated for the total sample and by level and years of experience. Multivariate analysis of variance and a Bonferroni-adjusted alpha level (P < 0.05) were used to test differences. Varsity rowers had significantly more rowing experience (0.5 years) before college, higher vertical jumps (3 cm), faster 2-km times (25 s), and lower endomorphic characteristics than novice rowers. Anthropometric and performance differences among rowers by years of experience were negligible with the exception of slower 2-km times (32 s) in rowers with no collegiate experience than rowers with collegiate experience. In conclusion, collegiate rowers differ to some extent in physical and performance characteristics by level and experience.